Bioanalytical challenges and unique considerations to support pharmacokinetic characterization of bispecific biotherapeutics. (19th March 2019) - Ma, Mark; Colletti, Kelly; Yang, Tong-Yuan; Leung, Sheldon; Pederson, Susan; Hottenstein, Charles S; Xu, Xiaohui; Warrino, Dominic; Wakshull, Eric
Compared with conventional (monospecific) therapeutics, bispecific protein therapeutics present unique challenges for pharmacokinetic (PK) characterization – namely, the characterization of multiple functional domains as well as the consideration of biotransformation or interference by the formation of antitherapeutic antibodies against each functional domain. PK characterization is essential to the success of the overall drug development plan and for molecules with multiple binding domains; multiple bioanalytical methods may be needed to answer critical questions for each phase of drug development. The number of bispecific protein therapeutics entering drug development continues to increase, and therefore, a bioanalytical strategy for the PK characterization of bispecific molecules and study of their in vivo structure–function relationship is needed. This review presents case studies and a regulatory perspective.